Targeted distribution - Ahmed, Akhter (International Food Policy Research Institute, 2000)
Despite recent economic growth, pervasive poverty and undemutrition persist in Bangladesh. According to the latest estimates, about half the population cannot afford an adequate diet (WGTFI 1994; Sen 1992; Ravallion and Sen 1996). Although long-term trends in the overall incidence of poverty show modest signs of improvement, the standard of living for those in extreme poverty has stagnated (Rahman 1994; Sen 1992). One-quarter of the population maintains a precarious existence. Chronically underfed and highly vulnerable, these people remain largely without assets (other than their own labor power) to cushion lean-season hunger or the crushing blows of illness, flooding, and other calamities. As a result, two-thirds of deaths among children under five years old are related to malnutrition (Hassan and Ahmed 1990).